DEKOMPOSISI SERASAH DAUN Avicennia marina DI PERAIRAN PULAU SEMBILAN KECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Saleha Bako; Yunasfi Djayus; Rusdi Leidonald (AQUACOASTMARINE, 2016)
The mangrove litter which has been decomposed contributes organic matter as food source for many species of fish and other organisms in the mangrove ecosystem. The purpose of this research is  to know the decompositio of A. marina litter leaf and to know the nutrient content of carbon (C), nitrogen (N) and phosphorus (P) in the A. marina litter leaf which been released during the decomposition time. This research was done at Pulau Sembilan, Pangkalan Susu Regency of Langkat North Sumatra Province during March until Mei  2016. This research used purposive sampling method at three stations and the determination of the station is done by seeing the availability of A. marina at the Pulau Sembilan. The results showed that the decomposition of A .marina litter leaf on day 75 are 11,13 in stasiun I, 10,94 in station II and 10,50 in III station. The fastest decomposition is the station I was  11,13 and the slowest decomposition is the station III was  10,50. The carbon during decomposition in 75 days are 10,46% at station I, 10,75% at station II and  11,03% at station III. Nitrogen which been decomposed on day 75 are 0,98% in station I, 1,18% in station II and 0,10% in station III. Phosphorus during decomposition in 75 days are  0,10% in station I, 0,11%  in station II and 0,10% in station III. Keywords : Pulau Sembilan, Decomposition, Avicennia marina